Web Site Contents of Municipal Transport Undertaking as a Modern Communication Tool for Enhancing Quality of Transport Services - Drdla, Pavel; Hrabacek, Jan (Communications - Scientific letters of the University of Zilina, 2005)
The paper deals with web site contents of Municipal Transport Undertakings. In the paper there are introduced kinds of information in use improving and intensifying communication between customers (passengers) and transport operators. These data come from research results of several Municipal Transport Undertaking web sites. There is also mentioned an informative minimum, which is found to be necessary and should not be omitted.